In vitro activities of eravacycline against clinical bacterial isolates: a multicenter study in Guangdong, China - Liao, Xiaoyan; Liang, Qianwen; Dai, Xinlu; Wu, Shigang; Duan, Chaohui; Luo, Zhaofan; Xie, Xiaoying (Frontiers in Microbiology, 2024)
IntroductionEravacycline (ERV), a novel tetracycline derivative, exhibits broad-spectrum antibacterial activity, but data on the bacterial activity against Chinese bacterial isolates are very scarce. This study aims to evaluate the activity of eravacycline against the common Gram-positive and Gram-negative bacteria isolates in Guangdong, China.MethodsThe clinical isolates were collected from four centers between 1 November 2023 and 31 January 2024, and the susceptibility of eravacycline (MIC50, MIC90, and MIC) was determined using broth microdilution as a reference method and E-TEST strips to evaluate their consistency. A total of 594 strains were collected from the four centers, including Staphylococcus aureus (n = 126), Enterococcus faecalis (n = 58), Enterococcus faecium (n = 29), Klebsiella pneumoniae (n = 136), Escherichia coli (n = 187), and Acinetobacter baumannii (n = 58).Results and discussionThe MIC50 and MIC90 (mg/L) of eravacycline were 0.12 and 1 for S. aureus, 0.06 and 0.12 for E. faecalis, 0.06 and 0.5 for E. faecium, 0.25 and 0.5 for E. coli, 0.5 and 2 for K. pneumoniae, and 0.25 and 2 for A. baumannii. Based on the FDA and EUCAST breakpoints, the susceptibility of eravacycline against S. aureus was 46.03% vs. 83.33%, 56.90% vs. 94.93% against E. faecalis, and 62.07% vs. 79.31% in E. faecium. The susceptibility rates of E. coli and K. pneumoniae were 90.37% and 58.09, respectively. To evaluate the performance between the broth microdilution test (BMD) and ETEST methods, we compared essential agreement (EA), categorical agreement (CA), very major error (VME), and major error (ME). The results demonstrated that compared with BMD, eravacycline measured by ETEST had higher VME and ME referring to FDA breakpoints than EUCAST breakpoints in the Gram-positive isolates. Since there were no intermediate breakpoints for the eravacycline, the MIC values measured by the ETEST method might result in lower CA and higher VME and ME. This study provides MIC values of eravacycline against Gram-positive and Gram-negative pathogens in four hospitals in Guangdong Province, and eravacycline is an effective therapeutic candidate for common bacteria.